CENTRALIZATION OF SERVICE MANAGEMENT WORK EXPERIENCE OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - A. A. Tsidrenkov (Литьë и металлургия)
The advantages and disadvantages of centralization of the labor service division in the enterprise are considered in the article. Optimization of the number of labor service division of enterprise, tasks of the centralization of labor service are studied.